AB0125 CXCL17 IN RHEUMATOID ARTHRITIS: INTERFERONE-GAMMA INDUCIBLE EXPRESSION AND INHIBITION OF ANGIOGENESIS. (June 2019) - Kernder, Anna; Mucke, Johanna; Tang-Chieu, Long; Lowin, Torsten; Claßen, Tim; Sander, Oliver; Bleck, Ellen; Heier, Claudia; Pongratz, Georg; Schneider, Matthias; Vordenbäumen, Stefan
Abstract : Background: CXCL17 is the latest chemokine discovered and was reported to influence angiogenesis and monocyte trafficking 1-2 . Its role in rheumatoid arthritis (RA) has not been assessed so far. Objectives: To assess the role of CXCL17 and its putative receptor G-protein-coupled receptor 35 (GPR35) in RA. Methods: Synovial tissue from joint replacements of RA and osteoarthritis (OA) patients was used for CXCL17 and GPR35 immunohistochemistry and in-situ-hybridization/immunofluorescence double-stainings. CXCL17 concentration in the synovial fluid of RA and CXCL17 production by synovial fibroblasts and smooth muscle cells after stimulation with TNF-α, INF-γ and IL-1β was quantified by qPCR and ELISA. Angiogenesis was assessed by a human umbilical vein endothelial cell culture assay. Results: CXCL17 and GPR35 are widely expressed in the synovial membrane of RA compared to OA (p=0.006). Within the synovial membrane CXCL17-mRNA could be located to vascular smooth muscle cells. INF-γ significantly induced CXCL17-mRNA and protein production in RA synovial fibroblasts (1.88-fold, p=0.019 and 2-fold, p=0.0002 respectively) and rat smooth muscle cells (67-fold, p=0.02 and 3.7-fold, p<0.001). CXCL17 was detected in the synovial fluid of RA (mean 310 pg/ml). In vitro angiogenesis was inhibited by CXCL17. This effect was reversed by specific GPR35 antagonists. Conclusion: CXCL17 is abundant in RA synovial tissue, localizes to vascular smooth muscle cells and fibroblasts, and is inducible by INF-γ. Antiangiogenic properties are mediated by GPR35. CXCL17 and GPR35 may constitute a hitherto unrecognized regulatory protein in RA pathogenesis and therefore be interesting drug targets. References: [1] Pisabarro MT, Leung B, Kwong M, Corpuz R, Frantz GD, Chiang N, et al. Cutting edge: novel human dendritic cell- and monocyte-attracting chemokine-like protein identified by fold recognition methods. J Immunol Baltim Md 1950. 2006;176(4):2069–73 [2] Lee W-Y, Wang C-J, Lin T-Y, Hsiao C-L, Luo C-W. CXCL17, an orphan chemokine, acts as a novel angiogenic and anti-inflammatory factor. Am J Physiol Endocrinol Metab. 2013;304(1):E32-40. Disclosure of Interests: Anna Kernder Grant/research support from: GlaxoSmithKline and UCB Pharma for performing the LuLa-study., Johanna Mucke: None declared, Long Tang-Chieu: None declared, Torsten Lowin: None declared, Tim Claßen: None declared, Oliver Sander: None declared, Ellen Bleck: None declared, Claudia Heier: None declared, Georg Pongratz : None declared, Matthias Schneider Grant/research support from: GlaxoSmithKline and UCB Pharma for performing the LuLa-study., Speakers bureau: Chugai, Stefan Vordenbäumen: None declared